Degradation rate and weight loss analysis for freeze-dried, decellularized, and deproteinized bovine bone scaffolds - Vidarta, Ramadhan Pramudya; Kamadjaja, David Buntoro; Danudiningrat, Coen Pramono; Amir, Muhammad Subhan; Rizqiawan, Andra; Yuliati , Anita; Darwis, Darmawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Mandibular defects, often caused by trauma, tumors, infections, and congenital issues, are commonly treated with bone grafts. Tissue engineering plays a crucial role in bone reconstruction, with scaffolds such as deproteinized bovine bone matrix (DBBM), freeze-dried bovine bone (FDBB), and decellularized FDBB (Dc-FDBB) being studied for their efficacy. Decellularization reduces the antigenic potential of FDBB. These scaffolds are designed to degrade within the body. Purpose: To analyze the weight loss and degradation rates of FDBB and Dc-FDBB materials, using DBBM as a control. Methods: This in vitro experimental study, conducted over 2 months, employed a cross-sectional approach to analyze the weight loss and degradation rates of FDBB, Dc-FDBB, and DBBM scaffolds in a simulated body fluid (SBF) solution. Results: Under dynamic immersion conditions, DBBM exhibited the highest daily weight loss at 0.741% and a degradation rate of 0.466 mg/cm²/day, followed by Dc-FDBB at 0.568% and 0.418 mg/cm²/day and FDBB at 0.525% and 0.385 mg/cm²/day. Under static immersion conditions, DBBM also showed the highest weight loss at 0.255%, with a degradation rate of 0.165 mg/cm²/day, followed by Dc-FDBB at 0.245% and 0.163 mg/cm²/day, and FDBB at 0.168% with a degradation rate of 0.126 mg/cm²/day. Significant differences were observed between scaffold groups (p = 0.000). Conclusion: DBBM, Dc-FDBB, and FDBB scaffolds meet the optimal requirements for tissue engineering materials based on their weight loss and degradation rates. DBBM demonstrated the highest values among the scaffolds analyzed.